Ang Tubig-Balon Sa Ibabaw Ng Ating Dibdib - Vito Jr., Ronaldo Soledad (Likhaan: The Journal of Contemporary Philippine Literature; Vol 18 No 1 (2024): LIKHAAN 18 The Journal of Contemporary Philippine Literature, 2024)
Cesar was accustomed to being the go-to person for his brother Spanky and his wife Milicent whenever a crisis or problem arose at home. But one day, when his brother called to say that he and Milicent had gone to see Aling Trining, Cesar immediately sensed that something terrible had happened to his niece, Tanya. From that moment on, Cesar was determined to use every possible means to save his beloved niece.